CYTOKININS: DISTRIBUTION IN TRANSFER RNA SPECIES OF Escherichia coli - Armstrong, D. J. (1969)
This distribution of cytokinin activity in tRNA species of Escherichia coli has been determined. Cytokinin activity was restricted to tRNA species recognizing codons with the initial letter U. The following have been shown to contain a cytokinin: tRNA(Phe), tRNA(Leu) UUG, tRNA(Ser)UC(G)(A), tRNA(Tyr), and tRNA(Try). tRNA(Cys) was present in fractions with cytokinin activity but was not sufficiently pure to prove it to be active. One tRNA(Ser) UC(C)(U) species was inactive. All major tRNA species recognizing condons with initial letters other than U were devoid of cytokinin activity in the tobacco bioassay. The significance of these findings is discussed as providing a possible mechanism of quantitative modulation at the translation stage of gene-controlled protein biosynthesis.